2020
DOI: 10.1016/j.apsb.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Small interfering RNA for cancer treatment: overcoming hurdles in delivery

Abstract: In many ways, cancer cells are different from healthy cells. A lot of tactical nano-based drug delivery systems are based on the difference between cancer and healthy cells. Currently, nanotechnology-based delivery systems are the most promising tool to deliver DNA-based products to cancer cells. This review aims to highlight the latest development in the lipids and polymeric nanocarrier for siRNA delivery to the cancer cells. It also provides the necessary information about siRNA development and its mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(96 citation statements)
references
References 320 publications
(194 reference statements)
2
94
0
Order By: Relevance
“… 30 , 81 Microscopy studies demonstrated that the exosomes allow for membrane fusion and cytosol dumping of therapeutic cargos, 56 while resulting in ultra-high inhibition of tumor growth in in vivo tumor models. 30 While it is thought that endosome entrapment can allow for the slow release of stable siRNA into the cells, 82 our exosomes avoid endosome entrapment and create direct siRNA delivery to the cytosol of targeted cells for swift treatment. 56
Figure 5 Summary of previous animal trials to elucidate the processing and releasing of Survivin siRNA incorporated in the RNA nanoparticles The data is from models of non-small-cell lung, 82 breast, 30 and prostate 30 cancer.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 , 81 Microscopy studies demonstrated that the exosomes allow for membrane fusion and cytosol dumping of therapeutic cargos, 56 while resulting in ultra-high inhibition of tumor growth in in vivo tumor models. 30 While it is thought that endosome entrapment can allow for the slow release of stable siRNA into the cells, 82 our exosomes avoid endosome entrapment and create direct siRNA delivery to the cytosol of targeted cells for swift treatment. 56
Figure 5 Summary of previous animal trials to elucidate the processing and releasing of Survivin siRNA incorporated in the RNA nanoparticles The data is from models of non-small-cell lung, 82 breast, 30 and prostate 30 cancer.
…”
Section: Resultsmentioning
confidence: 99%
“… 30 While it is thought that endosome entrapment can allow for the slow release of stable siRNA into the cells, 82 our exosomes avoid endosome entrapment and create direct siRNA delivery to the cytosol of targeted cells for swift treatment. 56
Figure 5 Summary of previous animal trials to elucidate the processing and releasing of Survivin siRNA incorporated in the RNA nanoparticles The data is from models of non-small-cell lung, 82 breast, 30 and prostate 30 cancer. RNA nanoparticles harboring Survivin siRNA were loaded into exosomes and decorated with either epidermal growth factor (EGFR) or prostate-specific membrane antigen (PSMA) RNA aptamers and delivered to prostate cancer, triple negative breast cancer (TNBC), and non-small-cell lung cancer (NSCLC) tumors in mice.
…”
Section: Resultsmentioning
confidence: 99%
“…Cationic liposomes are one of the most studied nanocarriers in gene therapy (Charbe et al, 2020 ). Our previous studies have demonstrated that LPD nanoliposomes can deliver siRNA efficiently and the high efficacy of LPD nanoliposomes was attributed to the high PEG density and sheddable PEG of LPD nanoliposomes (Gao et al, 2011 , 2012 , 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In any case, if the target tissue is not the lung, transfer to the lung must be inhibited. Other problems include capture by the reticuloendothelial system [ 90 , 91 ]. Therefore, it is necessary to devise ways to promote transfer to the target tissue while increasing blood retention.…”
Section: In Vivo Fatementioning
confidence: 99%